Legal Constipation on Protecting the Rights and Conditions of Victims of Human Trafficking Criminal Acts through The Implementation of Restitution - Ansari, Muhammad; Budianto, Azis (Journal of Comprehensive Science, 2024)
Inadequate efforts have been made to restore the rights and conditions of victims of human trafficking. This essay will look at the protection offered in order to better understand how victims of human trafficking crimes have not had their rights and losses satisfied. It takes a sociological-legal approach. The analysis of the available data indicates that the effective implementation of the protection of the rights of human trafficking victims has been hampered by the restitution regulations' lack of clarity regarding the amount and the regulation of substitute punishment for restitution. Victims of human trafficking may endure material, emotional, and bodily agony as a result of this crime against humanity. Moreover, it is challenging for victims and law police to record or.